A bifunctional cationic metal–organic framework based on unprecedented nonanuclear copper(ii) cluster for high dichromate and chromate trapping and highly efficient photocatalytic degradation of organic dyes under visible light irradiation. Issue 27 (25th June 2018) - Zheng, Tian-Rui; Qian, Lin-Lu; Li, Min; Wang, Zhi-Xiang; Li, Ke; Zhang, Ya-Qian; Li, Bao-Long; Wu, Bing
Abstract : A bifunctional cationic MOF showed fast and highly efficient Cr2 O7 2− and CrO4 2− trapping, and highly efficient photocatalytic activity. Abstract : A bifunctional cationic metal–organic framework [Cu9 (OH)6 Cl2 (itp)6 (1, 4-bdc)3 ](NO3 )2 (OH)2 ·20H2 O n (1-NO 3 -OH ·20H 2 O ) was synthesized and characterized (itp = 1-imidazol-1-yl-3-(1, 2, 4-triazol-4-yl)propane, 1, 4-bdc = 1, 4-benzenedicarboxylate). In1-NO 3 -OH ·20H 2 O, three [Cu3 (μ3 -OH)(μ2 -OH)] trimeric clusters are bridged by two μ3 -Cl and form a [Cu9 (μ3 -OH)3 (μ2 -OH)3 (μ3 -Cl)2 ] cluster. Such a nonanuclear copper(ii ) cluster [Cu9 (μ3 -OH)3 (μ2 -OH)3 (μ3 -Cl)2 ] has not been reported till now, at least to the best of our knowledge.1-NO 3 -OH ·20H 2 O showed a 6-connected 2D 3 6 -hxl net based on a nonanuclear copper(ii ) cluster [Cu9 (μ3 -OH)3 (μ2 -OH)3 (μ3 -Cl)2 ].1-NO 3 -OH·20H 2 O is also the first 2D 3 6 -hxl net-based nonanuclear cluster.1-NO 3 -OH (guest-free phase) showed fast and highly efficient Cr2 O7 2− and CrO4 2− trapping, and good recyclability for capturing Cr2 O7 2− and CrO4 2− . The adsorption capacities of1-NO 3 -OH to capture Cr2 O7 2− and CrO4 2− were 1.762 mol mol −1 (154.8 mg g −1 ) and 1.896 mol mol −1 (89.5 mg g −1 ), respectively, at a molar ratio of 1 : 2 (1-NO 3 -OH to 2.5 × 10 −3 mol L −1 Cr2 O7 2− or CrO4 2− ).1-NO 3 -OH exhibited the selective sorption of Cr2 O7 2− or CrO4 2− from a solution containing a mixture of Cr2 O7 2− or CrO4 2− and a ten-fold molar amount of ClO4 −, NO3 −, Cl −, BF4 − or a five-fold molar amount of mol L −1 SO4 2− .1-NO 3 -OH could capture 87.9% dilute Cr2 O7 2− or 91.8% dilute CrO4 2− at an equimolar1-NO 3 -OH to 20 ppm Cr2 O7 2− or CrO4 2− .1-NO 3 -OH ·20H 2 O exhibited a highly efficient photocatalytic degradation of the cationic organic dyes methylene blue (MB) and rhodamine B (RhB) under visible light irradiation, and was shown to be a good photocatalyst for photocatalytic degradation of the cationic organic dyes.